(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The aim of this research was to reveal an impact of anemia on the quality of life (QL) score, as well as on different subscales of children’s QL. The subjects of the research were 3 months–3 years old 100 children selected from two pediatric polyclinics of Yerevan. QL were measured by QUALIN questionnaire. A significant decrease in the total score and other domains of the QUALIN questionnaire scores were indicative for an impact of anemia on QL of the early aged children. Most affected subscale in case of anemia was «Ability to remain alone».